Sentient Ecologies Xenophobic Imaginaries of Landscape - Coțofană, Alexandra (Berghahn Books, 2022)
Employing methodological perspectives from the fields of political geography, environmental studies, anthropology, and their cognate disciplines, this volume explores alternative logics of sentient landscapes as racist, xenophobic, and right-wing. While the field of sentient landscapes has gained critical attention, the literature rarely seems to question the intentionality of sentient landscapes, which are often romanticized as pure, good, and just, and perceived as protectors of those who are powerless, indigenous, and colonized. The book takes a new stance on sentient landscapes with the intention of dispelling the denial of "coevalness" represented by their scholarly romanticization.